Black Lives Matter - Paulo, Avner; de Souza, Carlos Eduardo Oliveira; Lima e Silva, Bruna Guimarães; Schiavoni, Flávio Luiz; Siqueira, Adilson (Anais do Simpósio Brasileiro de Computação Musical (SBCM), 2019)
The Brazilian police killed 16 people per day in 2017 and 3/4 of the victims were black people. Recently, a Brazilian called Evaldo Rosa dos Santos, father, worker, musician, and black, was killed in Rio de Janeiro with 80 rifle bullets shot by the police. Everyday, the statistics and the news show that the police uses more force when dealing with black people and it seems obvious that, in Brazil, the state bullet uses to find a black skin to rest. Unfortunately, the brutal force and violence by the state and the police to black people is not a problem only in this country. It is a global reality that led to the creation of an international movement called Black Lives Matter (BLM), a movement against all types of racism towards the black people specially by the police and the state. The BLM movement also aims to connect black people of the entire world against the violence and for justice. In our work, we try to establish a link between the reality of black people in Brazil with the culture of black people around the world, connecting people and artists to perform a tribute to the black lives harved by the state force. For this, the piece uses web content, news, pictures, YouTube’s videos, and more, to create a collage of visual and musical environment merged with expressive movements of a dance, combining technology and gestures. Black culture beyond violence because we believe that black lives matter. such as the Ku Klux Klan, which bring the black population of the world into concern for possible setbacks in their rights. In Brazil, it is not different. Brazil is the non African country with the biggest afro descendant population in the world and one of the last country in the world to abolish slavery. Nowadays, a black person is 3 times more propense to be killed and most part of the murders in the country happened to afro Brazilians. Marielle Franco, a black city councillor from Rio, the only black female representative and one of seven women on the 51-seat council was killed in 2018. The killers were two former policeman. According to Human Rights Watch, the police force in the state of Rio de Janeiro, Brazil, killed more than 8,000 people between 2005 and 2015, 3/4 of them were black men. At the same time, the African culture strongly influenced the Brazilian culture and most part of the traditional Brazilian music and rhythms can be considered black music.